The Usual Suspects: Debunking the Myth About the aoCausesa of Terrorism (Global Journal of Human-Social Science, 2018)
What causes terrorism Myriad attempts have been made to categorize and explain the various causes of terrorism Countless books and journal articles in every academic discipline imaginable have been published associating terrorism with a litany of variables including poverty illiteracy inequality democracy authoritarianism and mental illness to name just a few